Peningkatan Hasil Belajar dengan Menggunakan Metode Cjpok pada Materi Negara-Negara Asean pada Mata Pelajaran Ilmu Pengetahuan Sosial pada Siswa Kelas VI - Dewi Sutria (Universitas Syiah Kuala, 2022)
This research is motivated by the lack of students' interest in Social Science lessons. The formulation of the research problem is whether the combination of the lecture method with the group work method has an effect on the Social Science learning outcomes of Class VI students? and how does the combined influence of the lecture method with the group work method on the learning motivation of Class VI students? This study aims to determine the effect of the combined lecture method with the group work method on the Social Science learning outcomes of Class VI students and to determine the effectiveness of the combined lecture method with the group work method in increasing the Social Science learning motivation of Class VI students. This research was conducted in July-October 2020, at SD Negeri 47/IV Jambi City. This type of research is classroom action research with 2 cycles consisting of planning, implementation, observation and reflection. Techniques and data collection tools in this study were field notes, list of student scores and student tests. The results of this study indicate that with the lecture method and group work method, student learning outcomes increase by 85%. It was concluded that the lecture method with the group work method could improve student learning outcomes and motivation.